Design and evaluation of self‑nanoemulsifying drug delivery systems for nebivolol hydrochloride (Asian Journal of Pharmaceutics (AJP), 2014)
Nebivolol hydrochloride (NEB) is third generation beta‑blocker, approved by the FDA to treat a hypertension. It’s aracemic mixture of a d‑Nebivolol and l‑Nebivolol. Oral delivery of the NEB shows a lower bioavailability due to its poorsolubility and permeability. In present study, self nano emulsifying drug delivery is formulated to increase the bioavailabilityof drug by increasing solubility and permeability through the gastro intestinal membrane. Excipients are selected on basisof results obtained from solubility studies of drug in various surfactants and oils. Selected system of oil, surfactant andco‑surfactant were screened for their miscibility and emulsification ability. The ternary phase diagram was constructed usingsystem Capmul MCM EP as oil, Tween‑60 as surfactant, Transcutol HP and PEG‑400 as co‑surfactant. Five compositionswere prepared from the self‑emulsifying area of the ternary diagram, loaded with NEB and then tested for robustness todilution, pH effect on globule size, mean globule size and polydispersity index (PDI), zeta potential, viscosity and drugrelease for the selection of optimized formulation. Further, the effect of viscosity and pH on the globule size and PDI ofoptimized SNEDDS was studied. In‑vitro drug release study was performed using dialysis bag method. Ex‑vivo drug releasestudies were also carried out to determine the permeability of drug loaded SNEDDS through the stomach and intestinalmembrane. The optimum concentration of a system determined Capmul MCM EP 25%, Tween‑60 50%, Transcutol HP12.5%, PEG‑400 12.5% with a globule size of 124.5 nm, cloud point at 770C and zeta potential of ‑5.123 mV. In‑vitro drugrelease study and ex‑vivo permeation study showed significant increase in dissolution rate and permeability respectively, ascompared to the drug suspension and marketed preparation (NEBISTAR™).Key words: Dissolution, ex‑vivo drug release, nebivolol hydrochloride, self‑nanoemulsifying drug delivery systems, solubility studies